Pengalaman Indonesia Menuju Demokrasi Beberapa Catalan Atas Pemilihan Umum Pada Masa Orde Lama, Orde Baru Dan Pasca Orde Baru - Sri Hastuti Puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2005)
General election iso ne of indicators where the pillar of democracy is conducted, it is also the implementation of human rigth, particularly, political right. In more general context, generalelection is an implementation of people's souvereignty, particularly in the perspective of representative democracy. Public participation can be used as a legal test for the implementation ofpeoples's souvereignty principle. It is assumed if public participation increases, this can reflect people's souvereignty. It also reflect the positive response to the use of people political right.